Association of Hearing Impairment and Subsequent Driving Mobility in Older Adults - Edwards, Jerri D; Lister, Jennifer J; Lin, Frank R; Andel, Ross; Brown, Lisa; Wood, Joanne M (The Gerontologist, 2017)
PURPOSE OF THE STUDY: Hearing impairment (HI) is associated with driving safety (e.g., increased crashes and poor on-road driving performance). However, little is known about HI and driving mobility. This study examined the longitudinal association of audiometric hearing with older adults' driving mobility over 3 years. DESIGN AND METHODS: Secondary data analyses were conducted of 500 individuals (63-90 years of age) from the Staying Keen in Later Life (SKILL) study. Hearing (pure tone average of 0.5, 1, and 2kHz) was assessed in the better hearing ear and categorized into normal hearing ≤25 dB hearing level (HL); mild HI 26-40 dB HL; or moderate and greater HI ≥41 dB HL. The Useful Field of View Test (UFOV) was used to estimate the risk for adverse driving events. Multivariate analysis of covariance compared driving mobility between HI levels across time, adjusting for age, sex, race, hypertension, and stroke. Adjusting for these same covariates, Cox regression analyses examined incidence of driving cessation by HI across 3 years. RESULTS: Individuals with moderate or greater HI performed poorly on the UFOV, indicating increased risk for adverse driving events (p < .001). No significant differences were found among older adults with varying levels of HI for driving mobility (p values > .05), including driving cessation rates (p = .38), across time. IMPLICATIONS: Although prior research indicates older adults with HI may be at higher risk for crashes, they may not modify driving over time. Further exploration of this issue is required to optimize efforts to improve driving safety and mobility among older adults.
Keywords: Male; lidé středního věku; senioři nad 80 let; Hearing impairment; Aged, 80 and over; Sex Factors; Age Factors; nedoslýchavost; Older drivers; Humans; Middle Aged; senioři; mužské pohlaví; Female; Automobile Driving; Aged; Driving mobility; Hearing loss; Proportional Hazards Models; ženské pohlaví; věkové faktory; Driving cessation; proporcionální rizikové modely; zdravotní stav; sexuální faktory; lidé; Hearing Loss; řízení motorových vozidel; Health Status